An improved lectin-based method for the detection of mucin-type O-glycans in biological samples - Lee, C.S.; Muthusamy, A.; Abdul-Rahman, P.S.; Bhavanandan, V.P.; Hashim, Onn Haji (2013)
Mucins and mucin-type glycoproteins, collectively referred to as mucin-type O-glycans, are implicated in many important biological functions and pathological conditions, including malignancy. Presently, there is no reliable method to measure the total mucin-type O-glycans of a sample, which may contain one or more of these macromolecules of unknown structures. We report the development of an improved microassay that is based on the binding of lectins to the unique and constant GalNAc-Ser/Thr structural feature of mucin-type O-glycans. Since the sugar-amino acid linkage in the mucin-type O-glycans is invariably cryptic, we first chemically removed the heterogeneous peripheral and core saccharides of model glycoconjugates before examining for their interactions using an enzyme-linked lectin assay (ELLA). Desialylation of the model glycoconjugates led to maximal binding of the lectins but additional treatments such as Smith degradation did not result in increased binding. Of the lectins tested for their ability to probe the desialylated O-glycans, jacalin showed the highest sensitivity followed by champedak galactose binding (CGB) lectin and Vicia villosa agglutinin. Further improvement in the sensitivity of ELLA was achieved by using microtiter plates that were pre-coated with the CGB lectin, which increased the specificity of the assay to mucin-type O-glycans. Finally, the applicability of the developed sandwich ELLA to crude samples was demonstrated by estimating trace quantities of the mucin-type O-glycans in the human serum.